Effect of Hole Geometry Shape in Vortex Generators on Fluid Output Temperature: Computational Fluids Dynamics Validation - Mohd Afzanizam Mohd Rosli; Singgih Dwi Prasetyo; Dominicus Danardono Dwi Prija Tjahjana; Alfian Fahrul Yuliansyah; Zainal Arifin (Universitas Sebelas Maret, 2023)
Several methods to enhance heat transfer can be classified into three categories: active, passive, or hybrid. Among these methods, Vortex Generators (VGs) are one passive heat transfer enhancement device widely used in heat exchangers. This study aims to explore the geometric shapes of VGs equipped with longitudinal holes and examine their influence on the outlet temperature of the fluid. For the analysis in this research, a three-dimensional Computational Fluid Dynamics (CFD) simulation using ANSYS Fluent software was employed. The increased heat transfer and flow resistance in the VG geometry were evaluated based on previous research for validation. The study results demonstrate that the simulation produces fluid outlet temperature values and velocity contours that closely resemble the results obtained from the reference study. The validation error of this research was found to be only 0.02%, indicating high quality and accurate simulation results. Furthermore, the study compared various geometries of the VG holes in the system. Among these geometries, hexagonal-shaped VG holes exhibited high-velocity contours on the VG side while achieving the lowest fluid outlet temperature at approximately 303.53 K. The findings of this study serve as a basis for further developments in enhancing the efficiency and performance of heat exchangers using VGs.